Selection and evaluation of reference genes for qRT-PCR in Inonotus obliquus - Li, Lulu; Guo, Xiaofan; Wang, Shouming (Frontiers in Microbiology, 2025)
Real-time quantitative reverse transcription PCR (RT-qPCR) is one of the most effective tools for studying gene expression. Inonotus obliquus is a rare and edible medicinal fungus. Selecting an appropriate reference gene is crucial for researching its gene function. In this study, we selected 11 potential reference genes of Inonotus obliquus. Subsequently, we applied GeNorm, NormFinder, and BestKeeper algorithms to evaluate the expression stability of these 11 reference genes. Under varying carbon sources, VPS exhibited good stability and was suitable as an internal reference gene. Under different nitrogen sources, RPB2 was the most stable reference gene. For varying growth factors, PP2A was the most stable reference gene. At different pH levels, UBQ showed the highest stability. Under different temperature conditions, RPL4 was the most stable. In different strains, RPL2 was the most stable reference gene, while VAS demonstrated the greatest stability across different growth stages. Overall, VPS was the most recommended reference gene for the entire sample set. This study provides a foundation for the further application of RT-qPCR in the gene expression analysis of Inonotus obliquus.